Rural Landscape as a Value of Cultural Heritage - Maria Wieruszewska (Wieś i Rolnictwo)
The Author – ethnologist and anthropologist of culture – defends the thesis that rural landscape is an important component of cultural heritage. Virtual “cyberspaces” as - sume the role of an alternative life environment. Physical space loses the basis for explaining the world and for shaping human experience. The degraded rural cultural landscape is the proof of erroneous conceptions and rural space gathers the effects of a deficit of sensibility to “long continuance”. In opposition to postmodernist assessments the Author objects to the attempts at destabilising culture. Culture is significant. The protection of rural landscape as a particularly sensitive and valuable quality has a sense. In the conclusion of her article the Author suggests that a more thorough humanistic reflection is needed to make it possible to optimally implement the recommendations of the European Landscape Convention.